Darolutamide-based triple therapy combined with PSMA imaging guided focal treatment in patients with prostate cancer: a multicenter retrospective study - Zhong, Dewen; Zhang, Ruochen; Wu, Jinling; Guo, Zhixun; Zhang, Yu; Zhou, Qinfei; Zou, Zijun; Lin, Deng; Lu, Zhonglei; Wang, Jiawen; Wu, Jinfeng; Ye, Liefu; et al. (Frontiers in Pharmacology, 2025)
BackgroundDarolutamide, a novel androgen receptor inhibitor, significantly improved outcomes in the ARASENS trial when combined with androgen deprivation therapy (ADT) and docetaxel chemotherapy for metastatic hormone-sensitive prostate cancer (mHSPC). In China, the regimen has been reimbursed since December 2023, expanding real-world accessibility. PSMA imaging–guided focal therapy enables precise localization of residual or oligometastatic lesions and may complement systemic control.ObjectiveTo evaluate the real-world efficacy and safety of darolutamide-based triplet therapy combined with PSMA imaging–guided focal treatment in patients with mHSPC.MethodsThis multicenter, retrospective study included 17 patients treated across three tertiary hospitals between June 2023 and June 2024. All patients received darolutamide (600 mg twice daily), ADT, and docetaxel (75 mg/m2 every 3 weeks for 4–6 cycles), followed 4–6 weeks later by focal therapy (surgery or radiotherapy) based on multidisciplinary team (MDT) assessment and PSMA IMAGING findings. Data collection followed STROBE recommendations. The primary endpoint was PSA90 response; secondary endpoints included PSA ≤0.2 ng/mL, PSA progression-free survival (PSA-PFS), radiographic PFS (rPFS), and safety.ResultsSeventeen patients with predominantly low- to intermediate-volume metastatic disease were analyzed. The PSA90 response rate was 94.1%, and 82.4% achieved PSA ≤0.2 ng/mL. Median PSA-PFS and rPFS were not reached at a median follow-up of 16 months. The 12-/18-month PSA-PFS rates were 88% and 65%, while the corresponding rPFS rates were 94% and 76%. Grade 1–2 myelosuppression (64.7%) and fatigue (47.1%) were most common; grade 3 neutropenia occurred in two patients (11.8%) without grade ≥4 events. Focal therapy was well tolerated, with no severe complications.ConclusionDarolutamide-based triplet therapy combined with PSMA-guided focal intervention achieved deep biochemical responses and durable disease control with manageable toxicity in real-world Chinese patients with mHSPC. The multicenter design and standardized methodology support the feasibility of this multimodal approach, which warrants validation in larger prospective studies.